2016
DOI: 10.1136/neurintsurg-2015-012233
|View full text |Cite
|
Sign up to set email alerts
|

Impact of immediate post-reperfusion cooling on outcome in patients with acute stroke and substantial ischemic changes

Abstract: The use of post-reperfusion cooling as a rescue treatment in patients with substantial ischemia at baseline might improve clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…4 As such, 16 clinical studies were included in this review. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] The flow of studies and reasons for exclusion are shown in ►Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4 As such, 16 clinical studies were included in this review. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] The flow of studies and reasons for exclusion are shown in ►Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
“…There were several small prospective case series describing specific interventions following ECR. 9,11,17 The results of the validity assessment are shown in Supplementary Table S1 (online only). The overall risk of bias amongst the included studies was high.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the neuroprotective strategies, TH has been attempted to evaluate the outcome benefits in experiments and clinical trials [4,9]. In a recent postreperfusion TH study, several patients (approximately 45%) had favorable outcomes based on the modified Rankin Scale 0, 1, 2 at 3 months despite low baseline alberta stroke pro-gram early CT score (ASPECTS) and large lesion volume ( > 80 mL) [34]. Recent EVT trials showed that EVT was useful for patients with a large core volume, and reperfusion rate was a predictor of good outcomes [35][36][37].…”
Section: Targeted Temperature Management During or After An Endovascumentioning
confidence: 99%
“…Neurocritical care for patients with massive ischemic stroke has also improved, especially in terms of neuroprotection and the antiswelling effect of therapeutic hypothermia [4]. While the therapeutic benefits of hypothermia on functional outcomes need to be further validated in prospective trials [5], there is evidence that it can reduce cerebral edema, reduce hemorrhagic transformation and improve outcomes, especially in those with complete reperfusion [4,6]. These developments have possibly increased the number of patients eligible for reperfusion therapies, while potentially reducing the number of patients that show malignant progression [7].…”
Section: Introductionmentioning
confidence: 99%